Effects of continuous and discontinuous non-relevant stimulus on creativity. Issue 2 (3rd April 2022) - Mille, Charles; Christmann, Olivier; Fleury, Sylvain; Richir, Simon
ABSTRACT: Innovation is made of different tasks from strategic positioning to the first phases of production. One of the main activities is the generation of ideas through different creativity phases. These creativity activities are carried out in numerous conditions and with different tools having more or less context and interactions. This study focuses on the influence of different non-relevant stimuli composing our environment on cognitive load and creativity. This experiment consists of two creativity tasks which consisted in providing answers to a given question using the visuo-spatial and audio-verbal area, with three stimulus appearance conditions: without, continuous, discontinuous. For the visuo-spatial task, participants have to illustrate their answers using an immersive drawing software. For the audio-verbal task, participants have to answer a question with a simple text editor software. Regarding the drawing task, results indicate that the discontinuous stimulus had decreased the number of ideas per participant. For the writing task, the stimulus had increased the intrinsic and extraneous cognitive load. This study reveals our creativity is under the influence of the different elements of our environment, the tool used and the task.